The Role of Public Speaking Skills in Improving the Performance of Hajj Guides - Desi Hasbiyah; Rofiah; Asep Gunawan; Falizar Rivani; Tohir Solehudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
This study explores the crucial role of public speaking skills in enhancing the effectiveness of Hajj guidance. As part of 21st-century competencies, public speaking not only facilitates communication but also serves as a strategic tool for delivering religious messages in a compelling and meaningful manner. In the context of Hajj guidance, strong public speaking skills help build confidence, reinforce authority, and prevent miscommunication. Through a literature review, this article examines key components of public speaking such as interpersonal communication, credibility of hajj pilgrimage guide as a speaker, content mastery, and the application of public communication psychology. The findings suggest that well-developed public speaking skills can improve communication effectiveness, support spiritual development, and contribute to a smooth and solemn Hajj experience.